Political Institutions and Policy Outcomes: What Are the Stylized Facts? - Torsten Persson; Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2001)
We investigate the effect of electoral rules and political regimes on fiscal policy outcomes in a panel of 61 democracies from 1960 and onwards. In presidential regimes, the size of government is smaller and less responsive to income shocks, compared to parliamentary regimes. Under majoritarian elections, social transfers are smaller and aggregate spending less responsive to income shocks than under proportional elections. Institutions also shape electoral cycles: only in presidential regimes is fiscal adjustment delayed until after the elections, and only in proportional and parliamentary systems do social transfers expand around elections. Several of these empirical regularities are in line with recent theoretical work; others are still awaiting a theoretical explanation.
Keywords: 330; Constitution; politics; presidentialism; electoral rule; government spending